Analysis of Financial Performance Towards Firm Value (Case Study at Building Construction Sub Sectors on IDX During Period of 2012-2018) - Henry Broto Seno; Hakiman Thamrin (Journal of Accounting and Finance Management, 2020)
These research aims to find out those impact from capital structure, profitability, liquidity, activity and company size on firm value. The population in this research were building construction sub-sector companies which registered in Indonesia Stock Exchange during period 2012 till 2018. The samples were determined by purposive sampling technique. These data analysis method used was panel data regression analysis. The selected mode used Fixed Effect Model. The results showed that capital structure, profitability, liquidity, activity and company size simultaneously had an impact on company value. Partially it was found that capital structure and profitability had positive influence on company value, activity and company size had negative influence on company value, while liquidity had none impact towards company value. The most influential variable was profitability with coefficient value was 43.38.